2023
DOI: 10.1093/glycob/cwac082
|View full text |Cite
|
Sign up to set email alerts
|

A combinatorial DNA assembly approach to biosynthesis ofN-linked glycans inE. coli

Abstract: Glycoengineering of recombinant glycans and glycoconjugates is a rapidly evolving field. However, the production and exploitation of glycans has lagged behind proteins and nucleic acids. Biosynthetic glycoconjugate production requires the coordinated cooperation of three key components within a bacterial cell: a substrate protein, a coupling oligosaccharyltransferase, and a glycan biosynthesis locus. While the acceptor protein and oligosaccharyltransferase are the products of single genes, the glycan is a prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Studies have demonstrated that protein yields can be enhanced by modifying or introducing supplementary promoter elements, or by adjusting gene copy numbers in the E. coli genome ( Yates et al, 2019 ; Jiang et al, 2021 ; Passmore et al, 2023 ). Although low gene copy numbers increase the stability of the expression system when acting as substrates or intermediates in the metabolic pathways involved in the normal metabolism of the host, it typically also results in a decrease in the yield of the target protein.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that protein yields can be enhanced by modifying or introducing supplementary promoter elements, or by adjusting gene copy numbers in the E. coli genome ( Yates et al, 2019 ; Jiang et al, 2021 ; Passmore et al, 2023 ). Although low gene copy numbers increase the stability of the expression system when acting as substrates or intermediates in the metabolic pathways involved in the normal metabolism of the host, it typically also results in a decrease in the yield of the target protein.…”
Section: Introductionmentioning
confidence: 99%